KEDUDUKAN DAN JUMLAH MAHAR DI NEGARA MUSLIM - Qodariah Barkah (Universitas Islam Negeri Jakarta, 2014)
The Position and Number of Dowries in Muslim Countries. The dowry has a significant role in a marriage. The obligation of the husband to provide a dowry for wife has led to various interpretations by mufassirand jurists. The Qur’an uses the term dowry gift accompanied with the words ma’rûf. Currently, various Muslim countries that have undertaken family law reform have included a dowry as one of the objects of the problem that must be given rules in detail, so that if in future there is a problem in the household and has been linked with the dowry then the matter can be settled by a judge.DOI: 10.15408/ajis.v14i2.1286